Perlindungan Hukum Penggunaan Senjata Api oleh Pejabat Imigrasi: Studi Kasus Indonesia dan Praktik Internasional - Fajar Fathony; Bachrul Amiq; Hananto Widodo (Jurnal Hukum Lex Generalis, 2025)
This paper is the result of descriptive research to examine the use of firearms by certain Immigration Officials within the scope of the Directorate General of Immigration in the implementation of Immigration functions in the field of law enforcement and state security. The purpose of this study is to provide an overview of the use of firearms in accordance with Law Number 63 of 2024 concerning the Third Amendment to Law Number 6 of 2011 concerning Immigration. The approach method used is the normative juridical method, namely the application of analysis based on a statutory approach and a comparative approach to international practice. The results of the study state that there is no regulation governing the use of firearms within the scope of the Directorate General of Immigration so that it must be made immediately in order to provide comprehensive legal protection in the implementation of the Immigration function.